2020
DOI: 10.1101/2020.05.20.105353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glyphosate Inhibits Melanization and Increases Susceptibility to Infection in Insects

Abstract: 13Melanin is a black-brown pigment found throughout all kingdoms of life playing diverse 14 roles including: UV protection, thermoregulation, oxidant scavenging, arthropod immunity, and 15 microbial virulence. Given melanin's broad functions in the biosphere, particularly in insect 16 immune defenses, it is important to understand how environmental conditions affect 17 melanization. Glyphosate, the most widely used herbicide, inhibits melanin production. Here we 18 elucidate the mechanism underlying glyphosate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 128 publications
(119 reference statements)
0
13
0
1
Order By: Relevance
“…Previously, we found that C. neoformans is encapsulated inside immune system-produced melanins during infection of G. mellonella , providing evidence that the melanin-based immune response is activated against C. neoformans in G. mellonella 30 (Figure 1A). To evaluate whether insect melanin encapsulation kills C. neoformans , we assessed viability using a GFP-expressing strain of C. neoformans , which expresses GFP under an actin promotor.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Previously, we found that C. neoformans is encapsulated inside immune system-produced melanins during infection of G. mellonella , providing evidence that the melanin-based immune response is activated against C. neoformans in G. mellonella 30 (Figure 1A). To evaluate whether insect melanin encapsulation kills C. neoformans , we assessed viability using a GFP-expressing strain of C. neoformans , which expresses GFP under an actin promotor.…”
Section: Resultsmentioning
confidence: 54%
“…Infection of G. mellonella larvae was performed as previously described 30 . Briefly, washed C. neoformans or C. albicans cultures, resuspended to 10 7 cells/ml were injected in the right rear proleg of larvae ranging from 175 to 225 mg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The health of insects is threatened by chemicals (1,2), and microbial pathogens (3,4), especially insect-pathogenic fungi, which are important regulators of natural insect populations (5,6). In addition, warming temperatures and human mediated radiation and chemical exposure may further exaggerate the negative influence on insect health (7,8), and there is thus a dire need for monitoring and studying insect health to preserve insect biodiversity.…”
Section: Main Textmentioning
confidence: 99%
“…The glyphosate effects vary in a species‐dependent manner, accordingly making it difficult to clarify similarities and distinctiveness resulting in herbicide exposure. It was already found that glyphosate exposure is associated with genotoxicity, oxidative damage, and imbalanced melanin synthesis leading to decreased melanin‐based immunity, health, and survival in insects (de Aguiar et al, 2016; Kaya et al, 2000; Qiao et al, 2016; Smith et al, 2021).…”
Section: Introductionmentioning
confidence: 99%